PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MATA PELAJARAN IPAS KELAS IV SD - Qifsy, Laura Amara; Hidayati, Abna; Saputra, Andra (Dharmas Education Journal (DE_Journal), 2023)
This research is considered extraordinary for making video media which is enlivened as a medium for learning science subjects in Review IV so that students and students can use media that is substantial, sensible and successful. This type of investigation into the progress of research is known as Investigation and Improvement (R&D). The progress model used in this progress is 4D. This 4D modeling consists of four steps, namely Define, Design, Develop, Disseminate. The aim of this research is to test and determine the development of animated video media in science and science subjects in class IV elementary school. Based on the evaluation results of the Media Validator, the Document Validator's average score of Media Validation is 4.8 "Very Valid". Results of Validator Material Validator Mean 4.74 "Very Good". This animated video media is considered "comfortable" based on real-world testing with an average value of 5.